2015
DOI: 10.1097/jnr.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Glycemic Control in Adolescents of Various Age Groups With Type 1 Diabetes

Abstract: Nurses should design specific interventions to improve glycemic control in adolescents of various age groups with T1D that are tailored to their developmental needs. For adolescents with T1D aged 10-12 years, nurses should actively assess family conflict and provide necessary interventions. For adolescents with T1D aged 13-18 years, nurses should exert special efforts to improve their self-care behaviors. In addition, female adolescents aged 16-18 years should be considered an at-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Lastly, dividing participants into smaller age segments may have revealed different patterns of interactions between psychosocial variables and outcomes that did not appear in our models, as others have found age to act as a moderator of the family functioning-adherence-metabolic control associations [ 76 ], and that developmental needs and reliance on caregivers vary greatly throughout the course of adolescence [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, dividing participants into smaller age segments may have revealed different patterns of interactions between psychosocial variables and outcomes that did not appear in our models, as others have found age to act as a moderator of the family functioning-adherence-metabolic control associations [ 76 ], and that developmental needs and reliance on caregivers vary greatly throughout the course of adolescence [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Epidemiology of Diabetes Interventions and Complications study, the long-term follow-up of the Diabetes Control and Complications Trial, reported a higher likelihood of microvascular and macrovascular disease in adolescents who had up to 6 years of suboptimal diabetes control (7). Furthermore, poor diabetes self-management behaviors and associated chronic suboptimal glycemic control can persist into adulthood (8)(9)(10).…”
mentioning
confidence: 99%
“…Differences were observed regarding how instruments were described in original studies and how these instruments were used in later studies. For example, in some later studies various subsets and adapted and/or updated items were generated that differed from the original tool [4,6,10,38,39,41,43,45,47,68,71,81,83,88,89,92,94,95,97,[102][103][104]107] or response options were added (i.e., "not applicable", "someone else" or "no one in the home") [5,47,63,83]. Contrary to original instructions of the DFRQ [8], in one study responders were requested to report per item which family member had most responsibility instead of who takes or initiates responsibility [47].…”
Section: Use Of Instruments Across Included Studiesdeviations From Or...mentioning
confidence: 99%
“…For none of the instruments costs were reported [8,40,50,52,58,78,84,91,100,107,[110][111][112]. Next to the language in which the questionnaire was developed, a few scales were (partly) translated into different languages in later studies (i.e., DRCS: Chinese [71]; DFRQ: Spanish [61] and presumably in the languages in the 19 countries involved in the study of Cameron et al 2008 [10]). q Mothers of children using pen therapy completed the DIS; Mothers of children using pump therapy completed the CSII-Use survey.…”
Section: Feasibilitymentioning
confidence: 99%